Inter-Professional-Compassionate pain management during endotracheal suctioning: a valuable lesson from a Chinese surgical intensive care unit - Ruan Qian-Wen; Khomapak Maneewat; Sangchan Hathairat (Sciendo, 2022)
To compare the effects of a pain management program and routine suctioning methods on the level of pain presence and agitation in Chinese adults admitted to the intensive care unit. To disseminate the results from the implementation of the evidence-informed pain management interventions for reducing pain presence and agitation during endotracheal tube suctioning (ETS) and translate the key finding to clinical nursing practice.